Two centuries of vaccination: historical and conceptual approach and future perspectives - Montero, David A.; Vidal, Roberto M.; Velasco, Juliana; Carreño, Leandro J.; Torres, Juan P.; Benachi O., Manuel A.; Tovar-Rosero, Yenifer-Yadira; Oñate, Angel A.; O'Ryan, Miguel (Frontiers in Public Health, 2024)
Over the past two centuries, vaccines have been critical for prevention of infectious diseases and are considered a milestone in the medical and public health history. The World Health Organization estimates that vaccination currently prevent approximately 3.5–5 million deaths annually, attributed to diseases such as diphtheria, tetanus, pertussis, influenza, and measles. Vaccination has facilitated the eradication of disabling and fatal pathogens, including the smallpox virus and wild poliovirus types 2 and 3. This narrative review offers a detailed journey through the history and advancements in vaccinology, tailored for healthcare workers. It traces the pivotal milestones, beginning with the variolation practices in the early 17th century, the development of the first smallpox vaccine, and the continuous evolution and innovation in vaccine development up to the contemporary era. We also briefly review immunological principles underlying vaccination, as well as the main vaccine types, with a special mention of the recently introduced mRNA vaccine technology. Additionally, we discuss the broad benefits of vaccines, including their role in reducing morbidity and mortality, and in fostering socioeconomic development in communities. Finally, we address the issue of vaccine hesitancy and discuss effective strategies to promote vaccine acceptance. Research, collaboration, and the widespread acceptance and use of vaccines are imperative for the continued success of vaccination programs in controlling and ultimately eradicating infectious diseases.